Heterogeneity of Human Mast Cells With Respect to MRGPRX2 Receptor Expression and Function - Varricchi, Gilda; Pecoraro, Antonio; Loffredo, Stefania; Poto, Remo; Rivellese, Felice; Genovese, Arturo; Marone, Gianni; Spadaro, Giuseppe (Frontiers in Cellular Neuroscience, 2019)
Mast cells and their mediators play a role in the control of homeostasis and in the pathogenesis of several disorders. The concept of rodent mast cell heterogeneity, initially established in the mid-1960s has been extended in humans. Human mast cells isolated and purified from different anatomic sites can be activated via aggregation of cell surface high affinity IgE receptors (FcRI) by antigens, superantigens, anti-IgE, and anti-FcRI. MAS-related G protein-coupled receptor-X2 (MRGPRX2) is expressed at high level in human skin mast cells (MCs) (HSMCs), synovial MCs (HSyMCs), but not in lung MCs (HLMCs). MRGPX2 can be activated by neuropeptide substance P, several opioids, cationic drugs, and 48/80. Substance P (5 x 10-7 M - 5 x 10-6 M) induced histamine and tryptase release from HSMCs and to a lesser extent from HSyMCs, but not from HLMCs and human cardiac MCs (HHMCs). Morphine (10-5 M - 3 x 10-4 M) selectively induced histamine and tryptase release from HSMCs, but not from HLMCs and HHMCs. SP and morphine were incomplete secretagogues because they did not induce the de novo synthesis of arachidonic acid metabolites from human mast cells. In the same experiments anti-IgE (3 g/ml) induced the release of histamine and tryptase and the de novo synthesis of prostaglandin D2 (PGD2) from HLMCs, HHMCs, HSyMCs, and HSMCs. By contrast, anti-IgE induced the production of leukotriene C4 (LTC4) from HLMCs, HHMCs, HSyMCs, but not from HSMCs. These results are compatible with the heterogeneous expression and function of MRGPRX2 receptor on primary human mast cells isolated from different anatomic sites.